Aktivitas Antitusif Dan Ekspektoran Ekstrak Etanol, Fraksi Polar-Semi Polar Herba Meniran (Phyllanthus niruri L.) Pada Marmut (Cavia porcellus) - Fakhruddin Fakhruddin; Arief Nurrochmad; Gunawan Pamudji Widodo (Fakultas Farmasi Universitas Setia Budi, 2017)
Phyllantus niruri L., is wild plants, has wide applications in traditional medicine. The purpose of this study is to evaluated antitussive, expectorant activity, and description antitussive mechanism of phyllantus herbs. Test animal male guniea pigs as many as 36 divided into 9 groups each consisting of 4 guinea pigs. The antitussive activity of ethanol extract and polar-semi-polar fraction be observed on percentage cough suppression by giving a citric acid 7.5% for 5 days. The Expectorant activity was evaluated with phenol red concentration in guinea trachea on 7 days. The mechanism description is evaluated by looking at the comparison of phyllantus herbs and combination ethanol extract phyllantus herbs and codeine modulated by the opioid receptor and glibenclamide modulated by the ATP sensitiv.e K+ channel. The research showed ethanol extract and polar-semi-polar fraction increased the suppression of citric acid induced by citric acid 7.5% and decreased the a supprssant of mucus secretion on evaluation of expectorant. Polar-semi-polar fraction 160 mg/kgBB showed the effective activity antitussive 63,57%. Polar-semi-polar fraction 80 mg/kgBB showed decreased phenol red secretion by 56,91%. This study provides evidence that phyllantus herbs can be used as an antitussive and a suppressant of mucus secretion. Phyllantus herbs not description on mechanism antitussive modulated by the opioid receptor and ATP sensitiv.e K+ channel. The antitussive mechanism may be modulated by other systemic nerves and peripheral nerves